Skema Bisnis Penyediaan Listrik untuk Kapal di Dermaga PT Pertamina Trans Kontinental dengan Metode Bisnis Model Canvas - Hamzah Hamzah; Tri Wahyu Adi (Pusat Riset dan Inovasi Nasional, 2026)
Indonesia is located along the Sea Lines of Communication (SLoC), a major maritime trade route passing through the Strait of Malacca and the South China Sea. Due to its highly strategic location for trade connectivity, many ships dock at Indonesian ports and operate their onboard generators while berthed, leading to increased CO₂ emissions and noise pollution. Therefore, it is necessary to develop port electricity infrastructure in the form of Onshore Power Supply (OPS) to replace the function of ship generators during docking. The OPS concept presents a new business opportunity that can improve port services while reducing CO₂ emissions and noise pollution. The business concept is developed using the Business Model Canvas (BMC) framework by Osterwalder (2010) along with supporting tools. The financial model is calculated using the Discounted Cash Flow (DCF) method to determine the variables and tariff, and is compared with the cost of electricity generated by ship generators during berthing. Using the BMC method, nine building blocks are identified to describe the OPS business scheme, along with an empathy map to develop a customer-centric business perspective. Based on the financial analysis using the DCF method, with an OPS tariff of IDR 2,466/kWh, the project yields a Payback Period of 8.11 years, an Internal Rate of Return (IRR) of 11.63%, and a positive Net Present Value (NPV) of IDR 9,346,693,566. In comparison, the estimated cost of ship-based power generation is IDR 4,249/kWh, which is more expensive than the OPS tariff. The results of this study indicate that the OPS business concept is feasible to be implemented in Indonesia.